Peran Model Science Environment, Technology and Society (SETS) Terhadap Pembentukan Karakter dan Motivasi Sustainibility Development Growt Society (SDGs) Siswa SMP - Pratiyaksi, Ni Made Diantari; Lasmawan, Wayan; Kertih, Wayan (Graduate School of Universitas Negeri Malang, 2024)
The SETS (Science, Environment, Technology, and Society) model science with environmental, technological and societal issues to enhance critical thinking, motivation, and concept application. This study examines its role in character formation and motivation towards achieving SDGs in SMP Negeri 2 Negara. Using a qualitative FAQ technique, it found 5 of 6 teachers actively use the SETS model, while one applies its principles unknowingly. This study highlight SETS’s potential in fostering global issue-based learning, environmental awareness, and social responsibility, encouraging broader adoption in education to advance SDGs achievement.